World Literature, Cosmopolitanism, Globality : Beyond, Against, Post, Otherwise - Müller, Gesine; Siskind, Mariano (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo Ser., 2019)
From today's vantage point it can be denied that the confidence in the abilities of globalism, mobility, and cosmopolitanism to illuminate cultural signification processes of our time has been severely shaken. In the face of this crisis, a key concept of this globalizing optimism as World Literature has been for the past twenty years necessarily is in the need of a comprehensive revision. World Literature, Cosmopolitanism, Globality: Beyond, Against, Post, Otherwise offers a wide range of contributions approaching the blind spots of the globally oriented Humanities for phenomena that in one way or another have gone beyond the discourses, aesthetics, and political positions of liberal cosmopolitanism and neoliberal globalization. Departing basically (but not exclusively) from different examples of Latin American literatures and cultures in globalized contexts, this volume provides innovative insights into critical readings of World Literature and its related conceptualizations. A timely book that embraces highly innovative perspectives, it will be a mustread for all scholars involved in the field of the global dimensions of literature.